Diagnostic accuracy for apical and chronic periodontitis biomarkers in gingival crevicular fluid: an exploratory study. (12th February 2016) - Baeza, Mauricio; Garrido, Mauricio; Hernández‐Ríos, Patricia; Dezerega, Andrea; García‐Sesnich, Jocelyn; Strauss, Franz; Aitken, Juan Pablo; Lesaffre, Emmanuel; Vanbelle, Sophie; Gamonal, Jorge; Brignardello‐Petersen, Romina; Tervahartiala, Taina; et al.
Abstract: Aim: The aim of this study was to assess the levels and diagnostic accuracy of a set of potential biomarkers of periodontal tissue metabolism in gingival crevicular fluid (GCF) from patients with chronic periodontitis (CP) and asymptomatic apical periodontitis ( AAP). Materials and Methods: Thirty one GCF samples from 11 CP patients, 44 GCF samples from 38 AAP patients and 31 GCF samples from 13 healthy volunteers were obtained ( N  = 106). Matrix metalloproteinases (MMPs) ‐2 and ‐9 were determined by zymography; levels of MMP‐8 by ELISA and IFMA and MPO by ELISA. IL‐1, IL‐6, TNF α, DKK‐1, Osteonectin, Periostin, TRAP‐5 and OPG were determined by a multiplex quantitative panel. Statistical analysis was performed using linear mixed‐effects models. Results: The MMP‐9 and MMP‐8 were higher in CP, followed by AAP, versus healthy individuals ( p  < 0.05). ProMMP‐2, MPO, IL‐1, IL‐6, PTN, TRAP‐5 and OPG were significantly higher in CP when compared with AAP and healthy patients ( p  < 0.05). The highest diagnostic accuracies were observed for ProMMP‐2, ProMMP‐9, MMP‐8 and TRAP‐5 (AUC > 0.97) in CP, and for the active form of MMP‐9 and MMP‐8 (AUC > 0.90) in AAP. Conclusion: Gingival crevicular fluid composition is modified by CP and AAP. MMP‐9 and MMP‐8 show diagnostic potential for CP and AAP, whereas MMP‐2 and TRAP‐5 are useful only for CP.